Grassland yield variation and botanical composition in mountainous areas of Norway - Lunnan T.; Todnem J. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
In Norway, farms in the mountain region need high amounts of conserved forage for the long winter period. The agricultural statistics shows that the grassland yields have stagnated or even decreased in some regions during the last 10-20 years. The farm size and milk production per farm has increased in this period, due to more use of rented land and buying of milk quota. In a new project, we estimate grassland yields to examine yield variations on the field level. The aim of the project is to explain yield variations under practical farming conditions and identify bottlenecks for the grass production. We make registrations of the yield by counting, weighing and sampling big bales. The botanical composition of the fields is examined by the dry weight rank method. Information about soil conditions, land and fertilizer use is gathered from the farmers and the advisory service. In the first year, six farms in three districts have participated in the project. Preliminary results show large yield variations. Poor drainage conditions are common in parts of many fields, limiting grass growth. Heavy traffic in connection with grass harvest and spreading of animal manure might also give yield reductions. The botanical analyses show that coach grass (Elymus repens) has a high proportion in many fields compared to other Norwegian investigations. We hope to extend this project the coming years to make a sound basis for good advices in grassland production.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)